2017
DOI: 10.3389/fphar.2017.00906
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of miR-26a-5p and miR-15b-5p Exosomal Expression Associated with Clopidogrel-Induced Hepatotoxicity in HepG2 Cells

Abstract: Clopidogrel is an essential antiplatelet drug used to prevent thrombosis complications associated with atherosclerosis. However, hepatotoxicity is a potential adverse effect related to clopidogrel therapy. Exosome-derived miRNAs may be useful for improved monitoring of drug response and hepatotoxicity risk. In the present study, the expression of several exosomal miRNAs (miR-26a-5p, miR-145-5p, miR-15b-5p, and miR-4701-3p) and cell-derived mRNA targets (PLOD2, SENP5, EIF4G2, HMGA2, STRADB, and TLK1) were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…However, extensive studies are needed to explore the participation of miR-4701-3p and miR-4793-3p in the regulation of SHU00238 on CRC tumor in animals and human (Liang et al, 2017). MiR-4701-3p, derived from exosomes, was shown to influence clopidogrel-induced liver injury, platelet reactivity, and drug-induced toxicity (Freitas et al, 2016;de Freitas et al, 2017). MiR-4701-3p was downregulated in patients with high risk of cadiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive studies are needed to explore the participation of miR-4701-3p and miR-4793-3p in the regulation of SHU00238 on CRC tumor in animals and human (Liang et al, 2017). MiR-4701-3p, derived from exosomes, was shown to influence clopidogrel-induced liver injury, platelet reactivity, and drug-induced toxicity (Freitas et al, 2016;de Freitas et al, 2017). MiR-4701-3p was downregulated in patients with high risk of cadiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-15a-5p was found to be involved in cell survival and apoptosis (Chen et al, 2017a; Chen and Tian, 2017; Zhou et al, 2018). In addition, dysregulated miR-15b-5p is also related to cellular toxicity (de Freitas et al, 2017; Chen et al, 2018b). Thus, we could conclude that the mmu-circRNA-013703 is involved in GE intoxication by sponging intoxication-related miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Via the transfection of cells with vectors containing a wild-type or mutated 3 UTR of HMGA1 or HMGA2 and reporter gene assays, several studies have demonstrated that miR-26a specifically targets well-conserved regions of the 3 UTRs of HMGA1 [87,89,90,92,95] and HMGA2 [91,93,94]. miR-26a downregulates HMGA1 at both the mRNA and protein levels, as assessed by qRT-PCR and Western blot analyses [87,90,92], while HMGA2 downregulation has only been validated at the protein level [93,222]. The role of the miR-26a/HMGA1 axis in the context of cancer has been extensively studied, and this axis has been shown to act on the proliferation and migration of pancreatic cancer [96], bladder cancer [95], breast cancer [92], lung adenocarcinoma [90], and osteosarcoma [89] cells.…”
Section: Hsa-mir-26amentioning
confidence: 99%